Information and resources important to the quality of life of people living with multiple sclerosis. Issue 2 (9th December 2020) - Bishop, Malachy; Rumrill, Stuart; McDaniels, Bradley; Li, Jian; Fraser, Robert; Rumrill, Phillip D.; Bhattarai, Muna; Park, Mirang
Abstract: Multiple sclerosis (MS) is a chronic, typically progressive immune-mediated disease characterized by inflammation and demyelination in the central nervous system (CNS), and is associated with a wide range of neurological, physical, and psychosocial effects. For people living with MS, access to relevant, timely, and accessible health information and resources may contribute to effective illness management, psychosocial health, and quality of life (QOL). In this study, we sought to increase understanding of the specific types of information most wanted by people with MS, as well as the sources and effects of this information. Specifically, we surveyed 748 adults with MS about (a) the sources from which they obtain information about MS, (b) the type of information that is most important in terms of improving their QOL, and (c) specific topics about which they would like to have more information, services, or resources. Content analysis of the qualitative results demonstrated the diversity of information sources accessed by people with MS and the importance of providing information through different formats and media. The participants prioritized information related to new MS medications and treatments, physical and mental health and wellness, and local opportunities for support. Implications for practicing rehabilitation counselors are discussed.